The Combined Effect of Bacteriophages and Antibiotics on Pseudomonas aeruginosa Biofilm - A. S. Gorshkova; V. V. Drwker; N. N. Sykilinda (Антибиотики и Химиотерапия, 2020)
Currently, the problem of nosocomial infections is of urgent concern. Pseudomonas aeruginosa is one of the key causative agents of this type of disease. The prospect of using bacteriophages in the prevention and control of infectious diseases is now being actively studied. The aim of the work is to study the effect of new bacteriophages on P.aeruginosa biofilm when used together with the antibiotic gentamicin. Cells of the laboratory reference strain P.aeruginosa PAO1 were grown in 96-well plates for a day, the resulting biofilms were treated with gentamicin in various concentrations, as well as bacteriophages AN14 and AN1. The degree of biofilm degradation was evaluated by staining the cells with crystal violet dye. The new lytic bacteriophages AN14 (Siphoviridae family), AN1 (Myoviridae family) used in the study, showed pronounced antibiofilm activity on the first day of exposure to P.aeruginosa biofilm (p<0.001). The destructive effect of gentamicin on biofilms increased when the concentration of the antibiotic was increased in the range of 2—16 mg/ml. Addition of lytic bacteriophages AN14 and AN1 enhanced the effect of the antibiotic (p=0.05). Thus, the combined use of lytic bacteriophages and antibiotics led to a more effective eradication of biofilms than when used separately.